The geometrical non-linear response of some pre-tensioned cable structures - Thew, Robert (1982)
A geometrical non-linear analysis of pre-tensioned cable structures is presented. Fully consistent methods of analysis are developed from earlier work involving minimum energy search techniques. The descent direction in the iterative process is determined by the method of conjugate gradients. The algorithm is suitable for both cable trusses and cable net structures and can include the effect of fully flexible boundaries. Convergence is obtained for all of the structural forms investigated for loadings up to the point where significant instability in the structure caused by member slackening occurs. An initial linear approximate analysis is shown to be of computational value as an initial starting point for the iterative process.